Negative Pressure Wound Therapy (NPWT)-assisted blowhole incisions in treating extensive subcutaneous emphysema: a literature review - Amestris, Eirene (Indonesian Vascular Access Association (IVAA), 2025)
Background: Subcutaneous emphysema (SE) is defined as the generation or infiltration of air in the subcutaneous tissues (beneath the dermal layer) of skin, cause by various etiologies. Untreated extensive SE can lead to respiratory and cardiovascular collapse. There are various treatments for treating SE. Blowhole incisions are considered one of the minimally invasive methods, with their variation by combining the incision with the usage of negative wound pressure therapy (NPWT). This literature study aims to evaluate the NPWT blowhole incisions in treating extensive subcutaneous emphysema Methods: Literature was sourced from PubMed, ProQuest, and Google Scholar databases. This review used case reports, case series, and systematic reviews, and each study underwent quality appraisal with the Joanna Briggs Institute (JBI) Critical Appraisal Checklist. In this study, we will compare the various settings used in NPWT-assisted blowhole incisions in treating extensive SE and the outcomes from the method used. The final list for review consisted of 14 studies. Results: Fourteen studies met the inclusion criteria. The most common causes of extensive subcutaneous emphysema were pneumothorax and rib fractures following chest trauma. The most frequently applied intervention was bilateral infraclavicular blowhole incisions measuring 3–5 cm, combined with NPWT at approximately −125 mmHg. Regression of subcutaneous emphysema, assessed clinically and/or with chest X-ray or CT, was typically observed within the first 24 hours, with NPWT removal possible after 96 hours. No complications or recurrences were reported across the included studies. Conclusion: NPWT-assisted blowhole incisions are a minimally invasive, safe, and effective method for managing extensive SE. Bilateral infraclavicular incisions measuring 3–5 cm combined with NPWT at continuous −125 mmHg appear to be a practical approach, typically resulting in regression within 4–72 hours, with device removal often after 96 hours. No significant complications or deaths were reported. The technique’s low cost, minimal infection risk, and practicality make it a viable alternative to more invasive interventions.